Mice - Frankel, Julie E.; Venezia, Mike (Chicago : Childrens Press, 1986)
Easy text and illustrations describe the activities of a variety of mice. Includes a list of words used in the text.
1.4
K-3
P-2.
Keywords: Mice -- Fiction; Mice -- Fiction